Formation process of relativistic electron flux through interaction with chorus emissions in the Earth's inner magnetosphere. Issue 11 (21st November 2015) - Omura, Yoshiharu; Miyashita, Yu; Yoshikawa, Masato; Summers, Danny; Hikishima, Mitsuru; Ebihara, Yusuke; Kubota, Yuko
Abstract: We perform test particle simulations of energetic electrons interacting with whistler mode chorus emissions. We compute trajectories of a large number of electrons forming a delta function with the same energy and equatorial pitch angle. The electrons are launched at different locations along the magnetic field line and different timings with respect to a pair of chorus emissions generated at the magnetic equator. We follow the evolution of the delta function and obtain a distribution function in energy and equatorial pitch angle, which is a numerical Green's function for one cycle of chorus wave‐particle interaction. We obtain the Green's functions for the energy range 10 keV–6 MeV and all pitch angles greater than the loss cone angle. By taking the convolution integral of the Green's functions with the distribution function of the injected electrons repeatedly, we follow a long‐time evolution of the distribution function. We find that the energetic electrons are accelerated effectively by relativistic turning acceleration and ultrarelativistic acceleration through nonlinear trapping by chorus emissions. Further, these processes result in the rapid formation of a dumbbell distribution of highly relativistic electrons within a few minutes after the onset of the continuous injection of 10–30 keV electrons. Key Points: Chorus emissions can accelerate electrons from tens of keV to several MeV within a few minutes A dumbbell distribution of relativistic electrons is formed by nonlinear trapping (RTA + URA) A numerical Green's function method for chorus wave‐particle interaction is formulated